A Critical Woman Barbara Wootton, Social Science and Public Policy in the Twentieth Century - Oakley, Ann (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Barbara Wootton was one of the extraordinary public figures of the twentieth century. She was an outstanding social scientist, an architect of the welfare state, an iconoclast who challenged conventional wisdoms and the first woman to sit on the Woolsack in the House of Lords. Ann Oakley has written a fascinating and highly readable account of the life and work of this singular woman, but the book goes much further. It is an engaged account of the making of British social policy at a critical period seen through the lens of the life and work of a pivotal figure. Oakley tells a story about the intersections of the public and the private and about the way her subject's life unfolded within, was shaped by, and helped to shape a particular social and intellectual context.